2016
DOI: 10.1038/srep27949
|View full text |Cite
|
Sign up to set email alerts
|

Ultracompact and high efficient silicon-based polarization splitter-rotator using a partially-etched subwavelength grating coupler

Abstract: On-chip polarization manipulation is pivotal for silicon-on-insulator material platform to realize polarization-transparent circuits and polarization-division-multiplexing transmissions, where polarization splitters and rotators are fundamental components. In this work, we propose an ultracompact and high efficient silicon-based polarization splitter-rotator (PSR) using a partially-etched subwavelength grating (SWG) coupler. The proposed PSR consists of a taper-integrated SWG coupler combined with a partially-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…In [39] a very compact PBS based on mode evolution was presented, with promising simulation results. In a further refinement [40], the same authors proposed a compact PSR based on a Reproduced with permission from [37].) similar approach.…”
Section: Polarization Managementmentioning
confidence: 99%
“…In [39] a very compact PBS based on mode evolution was presented, with promising simulation results. In a further refinement [40], the same authors proposed a compact PSR based on a Reproduced with permission from [37].) similar approach.…”
Section: Polarization Managementmentioning
confidence: 99%
“…Not only that most of such devices can be fabricated in single lithographic step but clever utilization of specific dispersion properties of SWG waveguides also allows for designing ultra-broadband devices. Among numerous applications of SWG technique, let us mention highly efficient fiber-chip couplers [1][2][3][4][5][6], broadband directional couplers [7] and multimode interference (MMI) couplers [8], polarization mode splitters [9][10][11], wavelength-division [2] and modedivision [12] multiplexers, optical delay lines [13], evanescent field sensors [14,15] and suspended membrane waveguides for mid-infrared applications [16]. Principles of operation and further applications of SWG devices have been recently reviewed in [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Since the first experimental demonstration of an optical waveguide with a subwavelength periodic core [4], these structures, also called subwavelength gratings (SWGs), have found many applications in integrated optics, for example as highly efficient fiber-chip couplers [3][4][5][6][7][8][9], low-loss waveguide crossings, evanescent field sensors [10,11], broadband directional couplers [12] and multimode interference (MMI) [13] couplers, polarization beam splitters [14][15][16], wavelength division [4] and mode division [17] multiplexers, delay lines [18], Fourier-transform spectrometers [19] and suspended (membrane) waveguides for mid-infrared applications [20]. Exhaustive reviews of SWG fundamentals and applications can be found in [21,22].…”
Section: Introductionmentioning
confidence: 99%